Longitudinal Evaluation of Cognitive Functioning in Young Children with Type 1 Diabetes over 18 Months. (20th January 2016) - Cato, M. Allison; Mauras, Nelly; Mazaika, Paul; Kollman, Craig; Cheng, Peiyao; Aye, Tandy; Ambrosino, Jodie; Beck, Roy W.; Ruedy, Katrina J.; Reiss, Allan L.; Tansey, Michael; White, Neil H.; et al.
Abstract: Objectives: Decrements in cognitive function may already be evident in young children with type 1 diabetes (T1D). Here we report prospectively acquired cognitive results over 18 months in a large cohort of young children with and without T1D.Methods: A total of 144 children with T1D (mean HbA1c: 7.9%) and 70 age-matched healthy controls (mean age both groups 8.5 years; median diabetes duration 3.9 years; mean age of onset 4.1 years) underwent neuropsychological testing at baseline and after 18-months of follow-up. We hypothesized that group differences observed at baseline would be more pronounced after 18 months, particularly in those T1D patients with greatest exposure to glycemic extremes.Results: Cognitive domain scores did not differ between groups at the 18 month testing session and did not change differently between groups over the follow-up period. However, within the T1D group, a history of diabetic ketoacidosis (DKA) was correlated with lower Verbal IQ and greater hyperglycemia exposure (HbA1c area under the curve) was inversely correlated to executive functions test performance. In addition, those with a history of both types of exposure performed most poorly on measures of executive function.Conclusions: The subtle cognitive differences between T1D children and nondiabetic controls observed at baseline were not observed 18 months later. Within the T1D group, as at baseline, relationships between cognition (Verbal IQ and executive functions) and glycemic variables (chronic hyperglycemia and DKA history) were evident. Continued longitudinal study of this T1D cohort and their carefully matched healthy comparison group is planned. ( JINS, 2016, 21, 293–302)